ON COLLISION OF SECONDARY NUCLEI OF COMET P/SHOEMAKER-LEVI 9 (1993E) WITH JUPITER - Churyumov, K. I.; Kruchinenko, V. G. (Одеські астрономічні публікації, 2017)
In July 1994 the comet P/Shoemaker-Levi which in July 1992 split in the Roche lobe of Jupiter onto 21 fragments, then collided with Jupiter at the altitude near – 45°. The consequences of this collision in the form of outbursts of brightness of the Jupiter satellites/ emergence of new structures in the cloud layer of Jupiter (type of the Great Red Spot ), generated of radiowaves and appearance of aurora, were observed at numerous world observatories, as well as from space probes. Since the moment of the split of comet P/Biela in 1846 onto two comets, astronomers have been already observing the 24th comets whose primary nucleus split onto secondary nuclei. The mechanism of destruction of the comet Shoemaker-Levi 9 was the tidal force of Jupiter which split the parental nucleus onto 21 icy pieces along one straight line. Prognosis of outbursts of brightness of Jupiter's satellites as a result of the light outburst in the atmosphere of the planet in the course of collision of the comet Shoemaker- Levi 9 with the latter is given. The Astronomical Observatory of Kiev University scientific program of observations of the collision of the comet Shoemaker-Levi with Jupiter is also presented.